(untitled) (Research, Society and Development, 2022)
Considering the increase in suicide cases reported daily, there was a motivation to investigate how nursing care is performed for patients with suicidal behavior who enter the emergency room. According to the World Health Organization (WHO), every year around 800 thousand people take their own lives worldwide. A number that represents almost one death every 40 seconds. The largest number of cases is led by India, with 258,000 suicides per year. The study aims to know the nursing care of people with suicidal behavior seen in the emergency room. It deals with a field research, of a descriptive character of qualitative approach. The research subjects were the nursing team of the emergency department of the General Hospital. The data collection was done through a questionnaire, composed of 4 open questions. Suicide is considered a public health problem, which increases considerably each day. Regardless of the factors that lead to suicidal behavior, be they due to mental disorders, depression or whatever the reason, suicidal behavior should be identified and treated.